The IMPLEMENTING FLIPPED LEARNING THROUGH ZOOM AND GOOGLE CLASSROOM IN UNIVERSITY IN BALIDURING COVID-19 : IMPLEMENTING FLIPPED LEARNING THROUGH ZOOM AND GOOGLE CLASSROOM IN UNIVERSITY IN BALIDURING COVID-19 - Gede Irwandika; Ni Made Verayanti Utami; Ni Nyoman Deni Ariyaningsih; Gede Dharma Arya Wicaksana (Focus Journal : Language Review, 2021)
Covid-19 Pandemic brought many changes of human life, including education. This study aimed to describe the implementation flipped learning through Zoom and Google Classroom in University in Bali during Covid-19 pandemic.This study was an descriptive study which was conducted in one of the universities in Bali in academic year 2019/2020 by using two research instruments, namely observation and interview. The result showed google Classroom was optimized in giving instruction or materials to the students via comment to make the instruction became accessible to all students. Then, Zoom meeting was used for class discussion after learning at home from instruction on Google Classroom. Some problems were occurred such as internet connection and limited non-verbal responses. However, In teacher’s perspective, flipped learning is really helpful because the teacher just need to give the material and instruction to students at home in Google Classroom and then at class discussion on Zoom, the teacher just need to act as facilitator.